The influence of entrepreneurship education on business performance and entrepreneurial self- efficacy of township entrepreneurs in Gauteng, South Africa - Sontsele, Nonkululeko (My University, 2022)
South Africa is faced with a high SMME failure rate, particularly those that have been functioning for fewer than 42 months, on the other hand, the rate of unemployment keeps rising, year on year, especially amongst the youth. Previous research in the field of entrepreneurship suggests that one of the primary reasons for the high failure rates of SMMEs in South Africa is a lack of access to entrepreneurship education. The purpose of this study is to investigate the influence of entrepreneurship education on business performance and entrepreneurial self-efficacy of township entrepreneurs in the Gauteng Province. Building from the existing body of literature on entrepreneurship education and business performance, the study further investigates the extent to which entrepreneurship education influences the entrepreneurial self-efficacy of the township entrepreneur. The study employs a cross-sectional quantitative methodology, which follows a post-positivist approach. Primary data, with a sample size of 150, was collected from SMMEs in the Gauteng townships through self- administered questionnaires. Data analysis included descriptive analysis, factor analysis, normality tests, correlations, and simple linear regression. Entrepreneurship education was the only predictor variable in the study, whilst business performance and entrepreneurial self-efficacy were the dependent variables. The results of the study found entrepreneurial education has a positive significant influence on business performance and entrepreneurial self-efficacy of the township entrepreneur. As the economic power hub of the country, Gauteng Provincial Government should apply a holistic view when formulating policies on business development support programmes in the future. This holistic view must include entrepreneurship education aimed at launching the entrepreneurial skills that will capacitate and equip new and existing SMMEs in the province to curb future failure rates. These skills should be tailor-made for existing businesses and should be inclusive of both business management skills and entrepreneurial skills. The study findings are pertinent as they could be used as a benchmark to guide this process.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements of the degree of Management Masters in Entrepreneurship and New Venture Creation.
Keywords: Entrepreneurial Education; Business Performance; Entrepreneurial –Self-efficacy; Township Entrepreneur; SDG-8: Decent work and economic growth